A Convergência da Contabilidade Pública Como Instrumento de Subjetivação Econômica Pelo Neoliberalismo: Uma Análise Foucaultiana - Souza, Frederico Pinto de (2024)
This thesis, considering the international convergence of public accounting, aims to characterize the arena of convergence of Brazilian public accounting, taking into account the discursive constructions that can be found in the situation and the possible resistance to the process. This thesis argues that national convergence is part of the constitution of neoliberal governmentality, which aims to shape government accountants and employees in general, through the use of accounting, towards a specific subjectivity (homo oeconomicus), establishing mechanisms and practices aimed at silencing other discourses of resistance. In order to achieve the proposed objectives, this thesis is based on Michael Foucault's analytics of power and uses the techniques of Foucauldian discourse analysis and situational analysis. These approaches allowed this thesis to consider the different discursive constructions present in the situation, including those related to resistance. Through the results obtained, it was possible to show that the convergence arena of Brazilian government accounting is characterized by the relationship between different social worlds (regulation, federal public administration, independent audit, international financial institutions and academia) and that the Comitê Permanente para Contabilidade Aplicada ao Setor Público (CP CASP) functions as an important convergence point. It has also been possible to characterize the dominant discourse in the situation and to verify that the convergence is not limited to the provision of accounting information, but is part of the establishment of a neoliberal governmentality that aims to introduce market concepts into the state, shaping the subjectivities of government employees (accountants and others) through competence-based accounting, capable of establishing quantifiable economic criteria that are the new guidelines for public policies. Finally, in the face of this movement, there was a certain resistance on the part of government accountants, who were subordinate to the discourse but unwilling to be submitted to the surveillance mechanisms.